Critical Analysis of the Selection Process for the General Election Commission Selection Team and the Election Supervisory Body in Indonesia - Diyanto, Diyanto (Strata Social and Humanities Studies, 2023)
This research seeks to analyze the selection process for the General Election Commission Selection Team and the Election Supervisory Body in Indonesia from a legal perspective. Through a normative method with a statutory and conceptual approach, the results of this research conclude that the formation of the General Election Commission (KPU) and Election Supervisory Body (Bawaslu) selection team as regulated in article 22 jo 118 of Law No. 7 of 2017 concerning Elections which the President formed is contrary to the duties and authority The President is regulated in the 1945 Constitution because no article or paragraph explains clearly and explicitly that the President's right to form the authority to create the selection team of KPU and Bawaslu and is not in accordance with the principle of legality or the principle of the rule of law. So, the formation of the selection team is based on article 22 jo 118 of Law No. 7 2017 concerning Elections is null and void along with legal regulations or derivative legal products. There is a legal violation by the President of Article 22E paragraph (5) of the 1945 Constitution.